Installation effects of supersonic inlets on next-generation SST turbofan engines - Adamidis, Stylianos; del Gatto, Dario; Mourouzidis, Christos; Brown, Stephen; Pachidis, Vassilios (MDPI, 2025)
This study explores inlet-related installation effects on next-generation SST aircraft, focusing on supersonic business jets. Using a comprehensive framework with consistent thrust/drag bookkeeping and realistic modeling of inlet losses, including operational limits for “buzz” and distortions, the inlet drag accounts for 8.8% to 14.2% of the installed net thrust during the supersonic segment of the mission. Variable airflow control technology is assessed, with a scheduling methodology developed to optimize the inlet operation by minimizing the installed SFC. The results show that this technology improves the installed SFC by 0.80% during supersonic cruise, enhancing the overall propulsion system performance.
Keywords: supersonic inlet; installation losses; bypass airflow control system; spillage drag; bypass drag; total pressure recovery; excess airflow management; installed SFC; next-generation SST